The Ability of 10th-Grade Students to Use Past Tenses in Writing Narrative Text in SMA Kartika Jaya 1-4 Pematangsiantar - Sianturi, Betty (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
This paper aims to investigate how well the 10th-grade students in SMA Kartika Jaya 1-4 Pematangsiantar able to use past tenses in writing a narrative text. This paper uses a descriptive quantitative method in which the data is the students’ narrative text consisting of 20 verbs in past tense and past perfect tense. Based on the investigation, it is found that the 10th-grade students in SMA Kartika Jaya 1-4 Pematangsiantar can use past tenses in writing narrative text and their ability is in the medium level. There is one student at the highest level or 2.86%, the students who are able at the medium level ability are thirty students or 85.72%, and the students who are able at the lowest level ability are four students or 11.42%. The mean is 67.57 and the standard deviation is 14.46 where the validity is 0.79 and the reliability is 0.88. By conducting this study, it is expected the teachers get an insight into measuring students’ ability to use past tenses in writing a narrative text.